The Cuban´s school weightlifter technical evaluation (Review) (Revista científica Olimpia, 2020)
The investigation "The technical evaluation of the school weightlifters in Cuba" it is a revision of the systems of evaluation techniques that they have been used by the Cuban Federation of Rising of Weights in the National School Games, The objective that the author thinks about in this revision it is to analyze the process of technical evaluation of the school weightlifter and to propose recommendations according to his limitations. The two evaluation systems are analyzed used in the last years, their limitations are declared, since they conceive the technical evaluation in a qualitative way, in a manual way. He/she is justified and it recommends, in a brief way how the process should be with the introduction of the Computer Technologies and the sport Biomechanics as science that he/she studies the movements in the sport.
Keywords: school weightlifters, technique, biomechanics, computer technologies